SEMIOTIC ANALYSIS OF SIGNS IN PUBLIC SPACES BASED ON PEIRCE'S THEORY - Amare Riefqi Amodia; Assyifa Khairunnisa; Fanny Khofifah Indrawati; Nadya Zulaika; Naylul Munji Vita Sari; Zabina Aulia Zahra (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Abstract This research examines the signs found in Bintaro Xchange Mall and KRL (Commuterline) and interprets the signs found through Peirce’s theory (1982). The main purpose of this research is to help readers have a better understanding of the meaning or message intended in signs that frequently appear in public places, especially in malls and KRL (Commuterline). This research uses a descriptive-qualitative approach by analyzing the signs found in Bintaro Xchange Mall and KRL (Commuterline). This research uses 30 signs, including 14 signs in Bintaro Xchange Mall and 16 signs in the KRL (Commuterline) station. The result of this study shows that all the signs found in the mentioned places correspond to Peirce’s semiotic theory, which consists of three key elements: the representamen, the object, and the interpretant. Each sign in Bintaro Xchange Mall and KRL (Commuterline) effectively utilizes these elements to communicate its intended message. Keywords: Semiotics, Sign, Peirce's theory, KRL, Bintaro Xchange mall, Public spaces. Abstrak Penelitian ini meneliti tanda-tanda yang terdapat di Bintaro Xchange Mall dan KRL (Commuterline) dan menginterpretasikan tanda-tanda yang ditemukan melalui teori Peirce (1982). Tujuan utama dari penelitian ini adalah untuk membantu pembaca agar lebih memahami makna atau pesan yang dimaksudkan dalam tanda-tanda yang sering muncul di tempat umum, khususnya di mall dan KRL. Penelitian ini menggunakan pendekatan deskriptif-kualitatif dengan menganalisa tanda-tanda yang terdapat di Bintaro Xchange Mall dan KRL. Penelitian ini menggunakan 30 tanda, diantaranya 14 tanda di Bintaro Xchange Mall dan 16 tanda di stasiun KRL. Hasil dari penelitian ini menunjukkan bahwa semua tanda yang ditemukan di kedua tempat tersebut sesuai dengan teori semiotika Peirce, yang terdiri dari tiga elemen kunci: representamen, objek, dan interpretant. Setiap tanda yang ada di Bintaro Xchange Mall dan KRL (Commuterline) secara efektif menggunakan elemen-elemen tersebut untuk mengkomunikasikan pesan yang ingin disampaikan. Kata kunci: Semiotika, Tanda, Teori Peirce, KRL, Bintaro Xchange Mall, Ruang publik.